Comparison of the Lipidomic Signature of Fatty Liver in Children and Adults: A Cross-Sectional Study. Issue 6 (19th June 2022) - Mann, Jake P.; Jenkins, Benjamin; Furse, Samuel; Snowden, Stuart G.; Alisi, Anna; Draijer, Laura G.; Karnebeek, Kylie; Kelly, Deirdre A.; Koot, Bart G.; Mosca, Antonella; Salvestrini, Camilla; van Mourik, Indra; et al.
ABSTRACT: Objective: Non-alcoholic fatty liver disease (NAFLD) is an increasingly common condition in children characterised by insulin resistance and altered lipid metabolism. Affected patients are at increased risk of cardiovascular disease (CVD) and children with NAFLD are likely to be at risk of premature cardiac events. Evaluation of the plasma lipid profile of children with NAFLD offers the opportunity to investigate these perturbations and understand how closely they mimic the changes seen in adults with cardiometabolic disease. Methods: We performed untargeted liquid chromatography—mass spectrometry (LC–MS) plasma lipidomics on 287 children: 19 lean controls, 146 from an obese cohort, and 122 NAFLD cases who had undergone liver biopsy. Associations between lipid species and liver histology were assessed using regression adjusted for age and sex. Results were then replicated using data from 9500 adults with metabolic phenotyping. Results: More severe paediatric NAFLD was associated with lower levels of long chain, polyunsaturated phosphatidylcholines (pC) and triglycerides (TG). Similar trends in pC and TG chain length and saturation were seen in adults with hepatic steatosis; however, many of the specific lipids associated with NAFLD differed between children and adults. Five lipids replicated in adults (including PC(36:4)) have been directly linked to death and cardiometabolic disease, as well as indirectly via genetic variants. Conclusion: These findings suggest that, whilst similar pathways of lipid metabolism are perturbed in paediatric NAFLD as in cardiometabolic disease in adults, the specific lipid signature in children is different.